Effect of Orange Peel Powder on Quality Characteristics of Pork Patties - B.V. Vivekananda Reddy; G.V. Bhaskar Reddy; T. Mounika; E. Naga Mallika; Bidyut Prava Mishra; M. Muthukumar; B. Eswara Rao (The Indian Veterinary Journal, 2023)
The pork patty is a handy meat product made from comminuted pork emulsion, which is prone to lipid oxidation during the storage process. The current research focuses on slowing down the process of lipid oxidation and microbial growth in pork patties. This was achieved by adding 1% orange peel powder and 0.5% orange peel extract to the pork patties. These treated patties were then packaged in aerobic conditions and stored in a refrigerated environment. The patties were evaluated for cooking parameters, proximate composition, physicochemical, microbial and sensory characteristics at regular intervals. The patties added with orange peel powder recorded significantly lower lipid oxidation and microbial counts than the control and synthetic antioxidants. Additionally, the patties with orange peel powder received superior sensory scores among all the treatments. In this study, it can be concluded that orange peel powder has potent antioxidant and antimicrobial activity in cooked pork patties under refrigeration.